Effect of additive metal salt on ionic liquid/Li4Ti5O12 electrode interfaces investigated by atomic force microscopy. (1st September 2022) - Bao, Yifan; Kitta, Mitsunori; Ichii, Takashi; Utsunomiya, Toru; Sugimura, Hiroyuki
Abstract: Ionic liquids (ILs) form layered solvation structures at IL/electrode interfaces relevant to many electrochemical applications. Recently, we observed a partially disturbed solvation structure at the 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMI-TFSI)/spinel lithium titanate oxide (Li4 Ti5 O12, LTO) electrode interface containing Li-salt and considered the Li + -ion transfer occurring at the interface as one plausible reason for this partial destruction. In this study, we investigated EMI-TFSI/LTO(111) interfaces with the addition of K-salt or Mg-salt by frequency modulation atomic force microscopy utilizing a quartz tuning fork. It is assumed that no ion-transfer occurs at these two interfaces. The laterally consecutive solvation structures were observed at both interfaces, which strongly supported our hypothesis. Additionally, a kink in the solvation structure was observed at the interface containing Mg-salt. These results offer a comprehensive understanding of the perplexing IL/electrode interfaces with an addition of metal salt.